Leveraging a Large Capital Investment to Develop Local Value Chains : Local Content in the Construction of Tanzania’s LNG Facility - World Bank Group (World Bank, Washington, DC, 2017)
The discovery of large, deep-sea, natural gas reserves in Southern Tanzania and plans for their development have sparked a national discussion about how Local Content can be maximized in a way that benefits the economy as a whole. Large-scale exploitation of Tanzania’s off-shore gas fields is justified only if much of the production can be exported. It is estimated that an investment in the range of 30 to 40 billion US dollars will eventually be needed to develop Tanzania’s Liquefied Natural Gas (LNG) production and export capability. However, funding will not be secured until a final investment decision (FID) is made, and negotiation delays and the general downturn in gas markets worldwide have pushed that decision out to 2018-2019. This interval puts Tanzania in a unique position from a development standpoint because it gives the country more time to prepare local firms and workers for greater integration in the gas value chain, which works to reduce the risk that the country faces of falling into the common Resource Curse trap. This study is a summary of analytical work performed by the World Bank Group (WBG) directed at helping the Tanzanians increase their participation in the construction of the LNG facility.